Wenyang Jiedu Tongluo formula ameliorates diabetic kidney disease by regulating JAML/SIRT1 signaling to improve lipid metabolism in db/db mice - Liu, Yutong; Chang, Tianying; Wang, Zikun; Liu, Hongkai; Li, Fan; Cui, Chengji; Cui, Yingzi; Zhang, Shoulin (Frontiers in Pharmacology, 2025)
IntroductionDiabetic kidney disease (DKD), a major microvascular complication of diabetes mellitus, is closely associated with abnormal lipid metabolism, which contributes to secondary renal injury. The JAML/SIRT1 signaling pathway plays a critical role in regulating renal lipid metabolism during DKD progression. To investigate the molecular mechanisms underlying the therapeutic effects of Wenyang Jiedu Tongluo Formula (WYJDTLF) on lipid metabolism in DKD, we conducted an animal study using db/db mice.MethodsThe mice were treated with WYJDTLF for 4 weeks, and its efficacy was evaluated through assessments of liver and kidney function, lipid profiles, and renal histopathology. Renal injury was examined using Hematoxylin and Eosin (H&E), Periodic Acid-Schiff (PAS), and Masson’s trichrome staining. Podocyte damage was assessed by quantifying the expression of podocyte marker proteins (Nephrin and NPHS2) using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Additionally, the expression levels of key proteins in the JAML/SIRT1 signaling pathway were analyzed via Western blot (WB).ResultsThe results demonstrated that WYJDTLF significantly improved liver and kidney function, reduced lipid deposition and inflammatory damage, and alleviated renal fibrosis and pathological injury. These effects were mediated through the regulation of the JAML/SIRT1 signaling pathway. Furthermore, WYJDTLF treatment upregulated the expression of Nephrin and NPHS2, indicating a protective effect on podocyte integrity.ConclusionOur team has revealed for the first time that the WYJDTLF can improve lipid metabolism abnormalities in db/db mice and alleviate diabetic kidney disease-induced renal pathological damage by inhibiting the JAML/SIRT1 signalling pathway. These findings provide a scientific basis for the potential application of WYJDTLF in the treatment of DKD.